On the road to sustainable transport: Acceptance and preferences for renewable fuel production infrastructure - Linzenich, Anika; Engelmann, Linda; Arning, Katrin; Becker, Tristan; Wolff, Michael; Walther, Grit; Ziefle, Martina (Frontiers in Energy Research, 2022)
To abate climate change and ameliorate the air quality in urban areas, innovative solutions are required to reduce CO2 and pollutant emissions from traffic. Alternative fuels made from biomass or CO2 and hydrogen can contribute to these goals by substituting fossil gasoline or diesel in combustion engines. Using a conjoint analysis approach, the current study investigates preferences of laypeople (n = 303) for alternative fuel production plants regarding siting location, plant size, raw material used in the production, and raw material transport. Location was most decision-relevant, followed by raw material transport, whereas plant size and type of raw material played a less prominent role for choice decisions. The best-case scenario from an acceptance perspective would be installing a rather small bio-hybrid fuel production plant in an industrial area (instead of an agricultural or pristine environment). No transport or transport via underground pipeline were preferred over truck / tank car or overground pipeline. The findings can be used to inform planning and decision making for the design of production networks of new fuel types.